Pareto reducible multicriteria optimization problems - Popovici, Nicolae (Optimization, 2005)
A multicriteria optimization problem is said to be Pareto reducible if its weakly efficient solutions actually are efficient solutions for the problem itself or for a subproblem obtained from it by selecting certain criteria. The aim of this article is to provide sufficient conditions for Pareto reducibility in a general framework, recovering in particular some known results concerning convex or explicitly quasiconvex criteria.